A Syntactical Analysis on Sentence Pattern Used in Sasha Sloan’s Song Lyrics - Harefa, Triputri; Siahaa, Sanggam; Sinaga, Asima Rohana (Universitas Pahlawan Tuanku Tambusai, 2025)
The research aimed to identify syntactical sentence patterns in Sasha Sloas' album, Only Child, using traditional grammar principles and Randolph Quirk's theory of sentence patterns. Data was collected through descriptive qualitative research and documentary analysis, using the Spotify application. The analysis revealed seven sentence patterns: Pattern 1, Pattern 2, Pattern 3, Pattern 4, Pattern 5, Pattern 6, and Pattern 7. Pattern 2 was the most frequently used, and sentence structure, including declarative and imperative sentences, plays a crucial role in conveying meaning and influencing the overall meaning of the text. The study used descriptive qualitative research and documentary analysis to analyze the lyrics of the album. The data was collected through the Spotify application.